Geometry Analysis of the Horizontal Curved Alinyemen Rail Road Cikampek – Cirebon Corridor - Nurullah Budisiswanto; Ahmad Syahirul Alim (Jurnal Impresi Indonesia, 2026)
The development of railway transportation in Indonesia requires continuous improvement in infrastructure quality to support higher train speeds while maintaining safety and comfort. PT Kereta Api Indonesia (Persero), through the Directorate General of Railways, plans to increase the maximum train speed from 120 km/h to 160 km/h. This study aims to analyze the railway track geometry on horizontal curve alignment in relation to the planned speed upgrade. The research was carried out on horizontal curve No. 21 at KM 201+064 to KM 201+584, located on the down track between Kertasmaya and Arjawinangun Stations in the Cikampek–Cirebon corridor (Operational Area 3 Cirebon), with a 1067 mm track gauge. The analysis includes curve radius, curve length, tangent angle, mid-ordinate, and rail superelevation, referring to PD No. 10A (2016) and Ministry of Transportation Regulations No. 32/2011 and No. 60/2012. The results show that the existing curve radius of 750 meters does not meet the minimum requirement of 800 meters for the 160 km/h design speed. Adjustments to superelevation and mid-ordinate values are required to ensure stability and ride comfort. Therefore, a realignment or redesign of the curve geometry is needed to achieve safe and efficient operation. This study is expected to serve as a technical reference for future railway speed enhancement projects and contribute to the advancement of railway engineering, particularly in track geometry analysis and design